Experiencing Becoming: The Initiation Process into Bektashi Tradition - Soileau, Mark (Religions, 2019)
Initiation into the Bektashi Sufi order is formalized as the initiate is led through a complex ritual form replete with symbols of death and rebirth, sacrifice, and integration that are enacted as the ritual is performed and in various ways experienced by the initiate. Once having entered and become a part of the order, then, the initiate encounters other cultural forms that reflect back upon the initiation ritual, such as poems that recount and provide commentary on it, contributing to his or her understanding of the experience of initiation as they too are performed in a communal context, and showing that integration into the order is an ongoing process. This paper analyzes the initiation ritual form with respect to the relationship between the cultural symbols presented in it and the experience it is intended to have on the initiate as he or she interacts with them. It further analyzes a particular poem that recounts the initiation ritual while adding impressions of the experiences evoked in it-experiences which meld with the initiate's own remembered experiences. Finally, it shows how these experiences are reinforced through the communal interaction that transpires as such poems are sung to music in a ritual context.